The Influence of the Implementation of the Merdeka Curriculum on Students' Social Awareness in Social Studies - Fitriyah, Saidatul; Oktafiana, Shinta (IAIN Madura, 2025)
This study investigates the effect of implementing Merdeka Curriculum on students' social sensitivity in social studies (IPS) at SMP Negeri 1 Pamekasan. Merdeka Curriculum aims to enhance students' critical thinking, communication, and teamwork skills while fostering social awareness. A quantitative method with an ex-post facto approach was used in this research. Data were collected through questionnaires distributed to a representative sample. The data were analyzed using simple linear regression, as the study involved two variables: the implementation of the Independent Curriculum (X) and students' social sensitivity (Y). The study is based on the Independent Curriculum theory from the Ministry of Education and the social sensitivity theory from David and Drost. The results indicate that the implementation of the Independent Curriculum at SMP Negeri 1 Pamekasan scored an average of 92.54, categorized as high. Students' social sensitivity in social studies also scored high, with an average of 92.56. Hypothesis testing confirmed a significant effect of the Independent Curriculum on social sensitivity, with an F-value of 48.012 and a significance value of 0.000 < 0.05. These findings suggest that the Independent Curriculum effectively improves students' social sensitivity and can guide future curriculum development